2014
DOI: 10.1007/s11605-013-2443-7
|View full text |Cite
|
Sign up to set email alerts
|

Value of Geriatric Frailty and Nutritional Status Assessment in Predicting Postoperative Mortality in Gastric Cancer Surgery

Abstract: This study shows a significant relationship between gastric cancer surgical mortality and geriatric frailty as well as nutritional status using a simple questionnaire. This may have implications in preoperative decision making in selecting patients who optimally benefit from surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 30 publications
1
76
1
1
Order By: Relevance
“…Most studies were observational (23 of 35) with a total of 1 153 684 patients available for the analysis. Cohorts were composed of patients undergoing lower gastrointestinal (GI) surgery (10 studies), upper GI surgery (6), mixed GI surgery (4), gynaecological surgery (6), urological surgery (4) and mixed abdominal surgery (6) ( Table  1)1 12, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were observational (23 of 35) with a total of 1 153 684 patients available for the analysis. Cohorts were composed of patients undergoing lower gastrointestinal (GI) surgery (10 studies), upper GI surgery (6), mixed GI surgery (4), gynaecological surgery (6), urological surgery (4) and mixed abdominal surgery (6) ( Table  1)1 12, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54.…”
Section: Resultsmentioning
confidence: 99%
“…The baseline characteristics of the remaining 63 patients are displayed in Table 1 and results of the GFI in Supplementary Table 2. Median age of included patients was 75 years (range 66-92) and 35% were women; 65% of patients were married, 27% was widower and 8% was unmarried. Median Charlson comorbidity index was 1 (range 0-6) and patients used a median of eight types of prescription medications (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Median eGFR at inclusion was 16 mL/min (range 5-34).…”
Section: Resultsmentioning
confidence: 99%
“…13,14 In geriatric oncology, several frailty screening tools are used to help identifying vulnerable patients, 15 including the GFI. 16,17 As patients with advanced renal failure experience a symptom burden and impairment of quality of life similar to that of patients with terminal malignancy, such tools could perhaps also be used to screen for potentially frail elderly among geriatric ESRD patients. 18 In this study, we aimed to assess whether the GFI can be used to distinguish fit older ESRD patients, likely able to tolerate and benefit from dialysis, from frail older patients who need further evaluation with a geriatrician's comprehensive assessment in a daily nephrology outpatient setting.…”
Section: Introductionmentioning
confidence: 99%
“…This questionnaire was used in a retrospective study to evaluate frailty assessment as a predictor for adverse outcome after gastric cancer surgery. In this recent study, incorporating 180 patients, increased GFI was significantly associated with postoperative morbidity and in-hospital mortality [30] . Prehabilitation A novel strategy for improving outcomes after surgery is by preoperatively correcting the reduced functional, nutritional, physical and neurophysiological state of patients: prehabilitation [45] .…”
Section: Mustmentioning
confidence: 87%
“…Increased scores are associated with more complications and increased length-of-stay [29] . A recently published study in which SNAQ was used to evaluate risks of adverse postoperative events after gastric cancer surgery showed that SNAQ ≥ 1 was associated with increased severe complications (i.e., Clavien-Dindo grade ≥ 3a, 35.7% vs 17.7%, P = 0.02) and in-hospital mortality (OR = 5.1, 95%CI: 1.01-23.8, P = 0.04) [30] . The detection of nutritional depletion is important, especially with…”
Section: Frailtymentioning
confidence: 99%